PENGARUH RASIONALITAS EKONOMI DAN KELOMPOK TEMAN SEBAYA TERHADAP PERILAKU KONSUMSI MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Wahidah, Nurul; Asriati, Nuraini; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
ABSTRACTThis study examines some of the major effects of economic rationality and peer groups on the consumption behavior of FKIP UNTAN economics education education. A common problem in this study is "How does the influence of economic rationality and peer groups to the consumption behavior of FKIP UNTAN students?". The purpose of this study is to analyze the Economic Rationality and Peer Groups against Student Consumption Behavior FKIP UNTAN Economic Education. The variables in this research are economic rationality, peer group, and consumption behavior. The approach used in this research using quantitative approach. Population in this research is all active student of Participation Grade Program (PAPK) odd semester of year of year 2014-2016 education of FKIP UNTAN working 202 student with sample 127 student taken at random. Data aids in this study is a questionnaire that has passed the validity and reliability test. Data analysis techniques used are quantitative descriptive techniques and multiple regression analysis techniques. (1) There is significant influence of Economic Rationality to Student Consumption Behavior of FKIP UNTAN Economic Education with significance level 0,005 <0,05 (2) No influence of Peer Group's significance to Student Economy Consumption Behavior FKIP UNTAN with significance level 0.141 > 0,05 (3) There is significant influence of Student Consumption Behavior of FKIP UNTAN Economic Education level of significance 0,005 <0,05.Keywords: Economic Rationality, Peer Group and Consumption Behavior